Bacterial Response after Exposure with Pure Metabolite Produced by Streptomyces sp. BL225 Isolated from Batanta Island's Leaf Litter - ARIF NURKANTO; ANDRIA AGUSTA; WELLYZAR SJAMSURIDZAL; HEDDY JULISTIONO (Indonesian Society for microbiology, 2013)
The objective of this research was to investigate bacterial response after treatment with active metabolite produced by Streptomyces sp. isolated from Batanta Island. Minimum inhibitory concentration (MIC) values of four clinically tested bacteria (Escherichia coli, Bacillus subtilis, Staphylococcus aureus, and Micrococcus luteus) were successfully determined in this research using microdilution method. Leakages of nucleic acids and proteins from the tested microbes were detected using UV/VIS spectrophotometry method at 260 and 280 nm. Uracil leakage was analyzed using HPLC. Morphological changes of the bacterial cells were observed using scanning electron microscope (SEM). A Streptomyces isolate BL225 was identified based on the 16S rRNA gene sequence (1500 bp). When tested agains microbes, the MICs values of this compound were between 16-64 µg mL-1. The results indicated leakages of protein, nucleic acid and uracil from E. coli and B. subtilis cells after treatment with pure metabolite isolated from BL225. Treatment using metabolite from BL225 also caused morphological changes and damages of the target bacterial cell. BL225 had been identified as a strain that has closed relation to Streptomyces badius (98.9%).